Application of unmmaned aerial vehicle (UAV), infiltration test and stream gauging for determining of hydrology paremeters at Kampung Lama Orang Asli, Kangkar Senangar, Batu Pahat Johor - Tajul Baharuddin, Mohamad Faizal; Yusoff, Nor Azizi; Embong, Zaidi; Lim, Alvin John Meng Siang; Hamidon, Nuramidah; Awang, Zarizi (Penerbit UTHM, 2020)
Knowledge of hydrology parameters characteristics is important for a number of reasons, including developing water resources strategies, particularly for conditions of rainfall; forming relationships between aquatic organisms and their environment; evaluating small to medium water supplies [1]. Hydrology parameters is a function of numerous variables that include factors such as topography, geology, soil, vegetation, and climate [2].